DEVELOPING UMKM ROSELLA BY ASSINGTING IN MAKING NIB AND HALAL CERTIFICATES - Afriani, Raden Irna; Rustandi, Tata; Arianti, Holifah; Aprilia, Reina Rianjani; Sutendi, Dedi; Wiguna, Wahyu (Yayasan Education and Social Center, 2025)
The food and drink industry is a downstream part of agriculture that plays a big role in promoting the use of local raw resources and making communities better places to live. Rosella flower (Hibiscus sabdariffa) is a commodit with development potential. li offers several health benefits and can be turned into different producis, such as herbal syrup. Mr. Hatibi is a seller in Mekarsari Village who uses rosella, but they still have problems with business legaliy, processing stills, and marketing of their products. The purpose of this communir; service activin is to help M. Hatibi's business grow by teaching him how to make rosella syrup and help them obtain a Buriness Identification Number (NIB) and halal certificate. Some of the tactics used include product processing training, buriness management workshops, development of production SOPS, digital marketing focus group discussions (FGDS), and regular evaluations. The findings of the activity revealed that the parmers have successfully obtained business licenses in the form of NIB and hala! certification. They can now mate and sell rosella syrup more widely, both in stores and online.